Linear discriminant analysis effect size (LEfSe) at various taxonomic levels (kingdom (k), phylum (p), class (c), order (o), family (f), genus (g), and species (s)) for broiler chickens fed diets containing fats of plant, animal, and insect origin. - Muhammad Rumman Aslam (22683482) (2025)
(A) bar graph of LDA scores for three groups (BSFL, plant oil, and animal fats), representing log10-transformed values for differentially abundant taxa; (B) cladogram illustrating phylogenetic relationships between taxa with significant differences in abundance across three groups (BSFL, plant oil, and animal fats). BSFL – basal diet with 100% black soldier fly (Hermetia illucens) larval fat; plant oils (SO – basal diet with 100% soybean oil; RO – basal diet with 100% rapeseed oil; PO – basal diet with 100% palm oil; PKFD – basal diet with 100% palm kernel fat distillate); animal fats (PF – basal diet with 100% poultry fat; PL – basal diet with 100% pig lard; BT – basal diet with 100% beef tallow).